Harmony of Nature: Building a Healthy Tourism Image Through Green Product Development - Setini, Made; Putra, Ida Bagus Udaya; Wahyuni, Ni Made; Asih, Daru; Triandini, Evi (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: Nowadays, village progress has also become a benchmark for the success of development in a country and region. The orientation of this study is to analyze the condition and potential of Subaya Village, Bangli, Kintamani, by using a mixed approach that combines field observation and SWOT analysis. The methodology applied involves in-depth observation of the village's strengths and weaknesses, as well as interviews with village officials and communities to identify opportunities and threats.Methodology: Applied using Analytical Hierarchical Process analysis involves in-depth observation of village strengths and weaknesses, as well as interviews with village officials and communities to identify opportunities and threats (SWOT-AHP). The main focus explored is to collect information from the local community and village officials regarding the potential of Subaya Village. Finding: This study shows that Subaya Village has significant strengths, such as abundant natural resources and rich local culture, which can be utilized for tourism development. However, there are weaknesses in infrastructure and limited human resources that need to be overcome. This research also identifies opportunities to develop ecotourism and community empowerment programs. Threats faced, such as climate change and competition from other regions, require appropriate mitigation strategies. Conclusion: Expected to provide a basis for the sustainable development of Subaya Village and improve community welfare through optimal utilization of local potential, and the utilization of the regional potential of Subaya Village through the development of tourism and ecotourism programs can enhance the welfare of the community while overcoming existing weaknesses and threats